Design of a Programmable System for Failure Modes and Effect Analysis of Steam-Power Plant Based on the Fault Tree Analysis - Soroor K. Hussain Al-Khafaji (Al-Khwarizmi College of Engineering – University of Baghdad, 2017)
In this paper, the system of the power plant has been investigated as a special type of industrial systems, which has a significant role in improving societies since the electrical energy has entered all kinds of industries, and it is considered as the artery of modern life.